2017
DOI: 10.1371/journal.pone.0177068
|View full text |Cite
|
Sign up to set email alerts
|

The thyroid cancer policy model: A mathematical simulation model of papillary thyroid carcinoma in The U.S. population

Abstract: BackgroundThyroid cancer affects over ½ million people in the U.S. and the incidence of thyroid cancer has increased worldwide at a rate higher than any other cancer, while survival has remained largely unchanged. The aim of this research was to develop, calibrate and verify a mathematical disease model to simulate the natural history of papillary thyroid cancer, which will serve as a platform to assess the effectiveness of clinical and cancer control interventions.MethodsHerein, we modeled the natural pre-cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 37 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…The diagnosis of thyroid nodules has increased in the last decade and, although most of them turned out to be benign, between 7 and 15% of the cases could present differentiated malignant neoplasms [ 1 ]. The increase in the incidence of differentiated thyroid tumors is largely due to overdiagnosis resulting from ultrasound screening and from cytological examination (needle aspiration) but also in part to a greater exposure to radiating agents [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…The diagnosis of thyroid nodules has increased in the last decade and, although most of them turned out to be benign, between 7 and 15% of the cases could present differentiated malignant neoplasms [ 1 ]. The increase in the incidence of differentiated thyroid tumors is largely due to overdiagnosis resulting from ultrasound screening and from cytological examination (needle aspiration) but also in part to a greater exposure to radiating agents [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…As for the articles that were included in the systematic review, an overview of each is given as follows. In Lubitz et al (2016), there is a mathematical approach using an ODE model with logistic growth for both benign and malignant thyroid tumors. In the text are modeled some characteristics as tumor volume over time, development rate, and detection rate among others.…”
Section: Resultsmentioning
confidence: 99%
“…A challenging aspect of the use of mathematical models concerns the estimation of parameters and in some papers of this review the realization of this process is observed (Barbolosi et al 2017;Chen et al 2007;Lubitz et al 2016). However, for accomplishing this task, a database and appropriate methods should be used.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations